Teachers and decision-making processes: An Italian exploratory study on individual and collaborative decisions - Parmigiani, Davide (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
This research was aimed at highlighting the decision-making processes of Italian teachers; in particular, we have focused on individual and collaborative decisions developed both during meetings and in the classroom. The study has underlined the features of teachers’ decisions when decisions are made in groups and individually. A questionnaire was administered to teachers (N=411) of Italian basic schools (pupils aged between 3 and 14 years old) and, in addition, we observed 18 meetings. The findings of this research indicate the main modalities for teachers’ decisions when they work individually or in groups. For group decisions, we emphasize the level of teachers’ involvement during meetings and how the participants process the information; from an individual point of view, we pinpoint the main features of instructional decisions and what types of heuristics and biases teachers use during instructional activities.